Mistress of the Ritz : [large type] a novel - Benjamin, Melanie, 1962- (Center Point Large Print, 2019)
"A novel based on the story of the extraordinary real-life American woman who secretly worked for the French Resistance during World War II--while playing hostess to the invading Germans at the iconic Hotel Ritz in Paris--from the New York Times bestselling author of The Aviator's Wife and The Swans of Fifth Avenue"--